Development of New Inhibitors of the Dihydroorotate Dehydrogenase Enzyme (DHODH) from Leishmania sp. (Research, Society and Development, 2021)
Leishmaniasis is a neglected disease and is considered one of the greatest endemic diseases in the world. The disease-causing parasites developed resistance against the drugs used in the disease's pharmacotherapy. Because of this, new compounds need to be devised to effectively treat this parasitosis. Therefore, in this paper we use molecular modeling approaches to design new inhibitors of the enzyme Dihydroorotate dehydrogenase (DHODH), a molecular target against leishmaniasis. Initially we used molecular modeling by homology to build the DHODH enzyme, later Metronidazole and Benznidazole were used as molecular frameworks for the development of new compounds. Then, the molecular docking method was applied to evaluate the interaction mode of the compounds with the binding site of the enzyme. The enzymatic model obtained 96% of its residues in favorable regions during its validation process. In the docking simulations, the compounds were able to interact favorably with the binding site and exhibit interactions with protein residues.